Legal aspects of merchandising in sports - Lukinović Mario; Opačić Ana; Milojević Irena (Oditor, 2020)
In the last thirty years, sport has undergone a significant transformation from a means of satisfying the need for physical activity, affirmation or competition with others to an extremely profitable industry. The development of sports has been favored by the development of mass media in terms of the creation of planetary sports idols. Consumers today are exposed to aggressive marketing policies, and manufacturers are trying to overcome information overload by exploiting recognizable symbols that consumers want to identify with through the emotional positioning of products. The authors point out the importance of merchandising as well as all the specificities that it manifests in its application in sports, with particular reference to the legal framework, and instruments for the further transfer of rights and protection of them.